2020
DOI: 10.1111/all.14339
|View full text |Cite
|
Sign up to set email alerts
|

Oscillometry improves earlier than spirometry after benralizumab initiation in severe asthma

Abstract: ent. 7,8 Thus, repurposing cysteamine as a treatment for asthma may be an effective and safe treatment, even for mild asthmatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…111 A study proposed the addition of oscillometry together with spirometry as it proved useful to assess earlier changes in responders to treatment with benralizumab. 112 Dunn et al 113 The role of eosinophils in personalized asthma treatment remains controversial. In a real-life study, Bagnasco et al showed no correlation between peripheral blood eosinophils count with the clinical, functional, and biological outcome changes in asthma patients.…”
Section: A S Thma D Iag Nos Is Precis I On Med I Cine and B I Omentioning
confidence: 99%
See 1 more Smart Citation
“…111 A study proposed the addition of oscillometry together with spirometry as it proved useful to assess earlier changes in responders to treatment with benralizumab. 112 Dunn et al 113 The role of eosinophils in personalized asthma treatment remains controversial. In a real-life study, Bagnasco et al showed no correlation between peripheral blood eosinophils count with the clinical, functional, and biological outcome changes in asthma patients.…”
Section: A S Thma D Iag Nos Is Precis I On Med I Cine and B I Omentioning
confidence: 99%
“…The clinical impact of SAD in asthma is further explored in the longitudinal study 111 . A study proposed the addition of oscillometry together with spirometry as it proved useful to assess earlier changes in responders to treatment with benralizumab 112 …”
Section: Asthma Diagnosis Precision Medicine and Biomarkersmentioning
confidence: 99%
“… 2 , 3 RWE studies report greater improvements in lung function, measured with spirometry and other techniques like oscillometry. 40 In our study, improvements exceed 320 mL, with improvement considered clinically relevant, as occurs in most RWE studies, where improvements have been observed even above 680 mL. 35 Exacerbations and lung function were evaluated in studies in SEA population with or without CRSwNP, obtaining better results in the subpopulation with CRSwNP.…”
Section: Discussionmentioning
confidence: 66%
“…For context, previous work also showed that oscillometry detected airway functional improvements in benralizumab-treated patients before or in the absence of spirometry improvements. 45 Taken together, these findings suggest that the mechanism of action of benralizumab may involve the peripheral airways, even in patients with substantial mucus plugging. Importantly, baseline VDP, and not R 5-19Hz , predicted response to treatment, suggesting that VDP may be a more sensitive measure of peripheral airway lumenization than R , where "lumenization" refers to the opening of the peripheral airways to the extent that inhaled gas can move into the corresponding lung segments.…”
Section: Discussionmentioning
confidence: 87%